2017
DOI: 10.18632/oncotarget.16591
|View full text |Cite
|
Sign up to set email alerts
|

A potential anti-tumor effect of leukotriene C4 through the induction of 15-hydroxyprostaglandin dehydrogenase expression in colon cancer cells

Abstract: Colorectal cancer (CRC) is one of the leading causes of cancer-related deaths worldwide. Cyclooxygenase-2, which plays a key role in the biosynthesis of prostaglandin E2 (PGE2), is often up-regulated in CRC and in other types of cancer. PGE2 induces angiogenesis and tumor cell survival, proliferation and migration. The tumor suppressor 15-hydroxyprostaglandin dehydrogenase (15-PGDH) is a key enzyme in PGE2 catabolism, converting it into its inactive metabolite 15-keto-PGE2, and is often down-regulated in cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Both receptors are not highly expressed in normal uveal tract [ 51 ], which suggests a role in early carcinogenesis. Of note, high CysLT 1 expression is associated with poor prognosis and reduced survival in both colorectal [ 28 ] and breast cancer [ 29 ], while CysLT 2 has been reported to have an anti-tumorigenic effect in colorectal cancer [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both receptors are not highly expressed in normal uveal tract [ 51 ], which suggests a role in early carcinogenesis. Of note, high CysLT 1 expression is associated with poor prognosis and reduced survival in both colorectal [ 28 ] and breast cancer [ 29 ], while CysLT 2 has been reported to have an anti-tumorigenic effect in colorectal cancer [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colon cancer is one of the leading causes of cancer-related deaths worldwide, and the incidence has been rising in recent years ( 25 27 ). The occurrence and development of colon cancer have been related to many factors, including living habits, genes and many other factors ( 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that CRC patients with low-CysLT 2 R and/or low-15-PGDH expression have a poor prognosis 12,20 . In this study, we noted that patients with high-GLI1 expression coupled with either low-CysLT 2 R expression or low-15-PGDH expression had poorer prognoses than patients with either low-GLI1 and low-15-PGDH expression or low-GLI1 and low-CysLT 2 R expression ( Fig.…”
Section: Gli1 Expression Is Negatively Correlated With Cyslt2r 15-pgmentioning
confidence: 99%
“…We determined whether Hh-GLI signalling was involved in the LTC 4 -induced 15-PGDH-promoted differentiation of CC cells 20 . Interestingly, LTC 4 stimulation significantly downregulated GLI1 expression at both the mRNA and protein levels compared with unstimulated HT-29 and Caco-2 cells (Fig.…”
Section: Ltc4-induced 15-pgdh Downregulates Gli1 In Colon Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation